2016
DOI: 10.5562/cca2885
|View full text |Cite
|
Sign up to set email alerts
|

Modified Bentonite with Dithizone as Nano Clay Mineral Adsorbent for Solid Phase Extraction of Silver Ions

Abstract: Abstract:In this work, a simple flow injection system incorporating a microcolumn of immobilized dithizone on bentonite coated with cetyltrimethylammonium bromide was combined with flame atomic absorption spectrometry (FAAS) for on-line separation/preconcentration and determination of trace amounts of silver in water. Dithizone was physically immobilized on the surfactant coated bentonite particles and was used as the adsorbent in the preparation of microcolumn. Silver ions were deposited by processing a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…FTIR measurements were carried out to demonstrate the chemical nature of the nano bentonite and to identify the possible interaction between Fe 3þ , Zn 2þ and Ni 2þ, and Nano bentonite [10]. The FT-IR spectra of Nano bentonite are shown in Figure 1.…”
Section: Ftir Spectramentioning
confidence: 99%
“…FTIR measurements were carried out to demonstrate the chemical nature of the nano bentonite and to identify the possible interaction between Fe 3þ , Zn 2þ and Ni 2þ, and Nano bentonite [10]. The FT-IR spectra of Nano bentonite are shown in Figure 1.…”
Section: Ftir Spectramentioning
confidence: 99%
“…Mudasir et al showed that dithizone-immobilized natural zeolite (13.1×10 -6 mol g -1 ) has higher capacity than activated natural zeolite (8.00×10 -6 mol g -1 ) to adsorb Hg(II) ion [9]. Shakerian et al reported that the adsorption capacity of dithizone-immobilized bentonite for Ag(II) was 7.2 mg Ag(II) per gram of adsorbent [10]. Parham et al confirmed that dithizone-immobilized cellulose acetate polymer membrane has capacity adsorption for Pb(II) and Cd(II)ions which were 787 and 195 mg g -1 , respectively [11].…”
Section: Introductionmentioning
confidence: 99%